Taoist Philosophy in Chinese Science Fiction: A Comparison between Zhuangzi and Broken Stars - Aiqing Wang (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
Chinese science fiction has been attaining global visibility since Liu Cixin’s trilogy entitled Remembrance of Earth’s Past. The trilogy’s English translator Liu Yukun has edited and rendered a science-fiction anthology that comprises sixteen novellas composed by fourteen Chinese novelists. Apart from a fecundity of imagination and richness of imagery-evoking depictions, narratives compiled in the anthology also epitomise Taoist philosophy conveyed in Zhuangzi, a Warring States (475-221 BC) treatise ascribed to an illustrious philosopher Zhuangzi. Philosophical constructs in the anthology can be exemplified by quintessential construals such as ‘non-action’, ‘resting in destiny’ and ‘self-so’, as well as mindset appertaining to temporal and aesthetic issues.